2014
DOI: 10.1111/aos.12370
|View full text |Cite
|
Sign up to set email alerts
|

Ocular diseases and 10‐year mortality: The Beijing Eye Study 2001/2011

Abstract: ABSTRACT.Purpose: To examine the relationship between major ocular diseases and mortality.Methods: The population-based longitudinal study Beijing Eye Study was performed in 2001 and repeated in 2011. The participants underwent a detailed ophthalmic examination at baseline in 2001. Results: Of 4439 subjects examined in 2001, 2695 (60.7%) subjects returned for the follow-up examination in 2011, while 379 (8.5%) subjects were dead and 1365 (30.8%) subjects were alive, however, did not agree to be re-examined. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
43
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 28 publications
3
43
0
1
Order By: Relevance
“…[3][4][5][6][7][8][9][10] It has been speculated that oxidation with aging and oxidative stresses on the lens 17 could explain some of the complex etiology of cataract. In addition, cataract is regarded as the translational ''window to the rest of the body,'' suggesting cataract perhaps is a biomarker for aging at the molecular, epigenetic, cellular, and clinical levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10] It has been speculated that oxidation with aging and oxidative stresses on the lens 17 could explain some of the complex etiology of cataract. In addition, cataract is regarded as the translational ''window to the rest of the body,'' suggesting cataract perhaps is a biomarker for aging at the molecular, epigenetic, cellular, and clinical levels.…”
Section: Discussionmentioning
confidence: 99%
“…2 There is consistent evidence showing that persons with cataract have a higher risk of mortality compared with persons without cataract. [3][4][5][6][7][8][9][10] Cataract surgery is the only effective treatment for people with cataract, and is the most commonly performed clinical procedure in the medical field. 11 In addition to improving visual function, some evidences suggest that cataract surgery is associated with better chances of survival, although this has yet to be conclusive.…”
mentioning
confidence: 99%
“…9,17,[30][31][32] Other recent studies by the Beijing Eye Study, such as the observed association between the estimated cerebrospinal fluid pressure and retinal vein diameter in arterial hypertension, and the 10-year mortality of ocular diseases, do not have a direct association with the topic of the current study. 33,34 From a practical point of view, one may raise the question whether brain imaging should be performed to exclude cerebral ischemic attacks in patients without glaucoma or diabetic retinopathy and who present with an incident RNFLD. The design of our study did not allow answering such a question.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have linked cigarette smoking to an increased risk of developing cataracts in men and women [19]. Several studies have indicated that GST enzymes may play a role in cataract predisposition with different GST phenotypes [16,[20][21][22][23] but no associations were found in another study [24].…”
mentioning
confidence: 99%